Is the TRIPS Agreement and its' safeguards still a stumbling block in fulfilling the right to health and if so what should be done? - Gill, Alison Elizabeth (Centre for Law and Society, 2026)
In order to meet the Millennium Development Goals by 2015 the world must radically rethink the means of achieving the targets set by these Goals. The developing world is crippled by poverty and disease; HIV/ AIDS is rife in Africa and is spreading at frightening speed to many other parts of the globe. World Health Organisation (WHO) figures suggest that in 2008 33 million people were infected with HIV. Chapter I shall consider the problem of the AIDS/HIV epidemic in more detail and the international response so far. The chapter shall then look at the various sources of international law within a human rights context to determine whether states have an obligation to do something about the disease.